2017
DOI: 10.7860/jcdr/2017/22302.9388
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Etiology of Pasteurella canis Biovar 2 Causing Dacryocystitis in HIV Patient: A Case Report and Review of Literature

Abstract: An adult 25-year-old male truck driver presented to Outpatient

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…For septic arthritis, prosthetic joint increases the risk of infection [ 2 ]. Specifically, in infection due to Pasteurella canis, there are reports in diabetic [ 3 , 4 ] and immunocompromised patients [ 5 , 10 , 16 ]. Our patient had risk factors like advanced age and a history of diabetes but she had no knee prosthetics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For septic arthritis, prosthetic joint increases the risk of infection [ 2 ]. Specifically, in infection due to Pasteurella canis, there are reports in diabetic [ 3 , 4 ] and immunocompromised patients [ 5 , 10 , 16 ]. Our patient had risk factors like advanced age and a history of diabetes but she had no knee prosthetics.…”
Section: Discussionmentioning
confidence: 99%
“…Human infection by Pasteurella canis is rare and there are reported cases of soft tissue infections [3][4][5][6][7], bacteremia [5,[7][8][9], eye infections [10,11], respiratory infection [8,9,12], septic arthritis [13,14], osteomyelitis [3,15], gastrointestinal infection [16], breast implant infection [17], and peritonitis [18]. The first-line treatment is with penicillins and alternatively with fluoroquinolone, doxycycline, or trimethoprimsulfamethoxazole [1].…”
Section: Introductionmentioning
confidence: 99%
“…The second study identified P canis as an important cause of conjunctivitis outbreak that was resistant to empirical treatment in a pediatric agency [8] . Lastly, ocular adnexal infection in the form of P canis dacryocystitis in a human immunodeficiency virus (HIV) positive patient was reported [9] . These cases seem to imply that immune naïve (newborns, and pediatric patients), and immunocompromised patients may be at increased risk for invasive infection.…”
Section: Discussionmentioning
confidence: 99%